Sistem Ekonomi Konvensional Dan Ekonomi Syari’ah Dalam Studi Islam - Andi Holilulloh (LP3M STITNU Al Hikmah Mojokerto, 2019)
Conventional economics is an economy that is quite foreign to Muslims in Indonesia, Sharia economics can also be interpreted as a collection of legal norms that originate from the Koran and the hadith that govern the economic affairs of mankind. The scholars, both salaf scholars of the four schools (Maliki, Hanafi, Shafi'i and Hambali) as well as contemporary scholars, all of them basically agreed on the prohibition of usury. Even scholars who allow bank interest, also forbid usury. Thus it can be understood that the difference in opinions of scholars is not a matter of prohibiting usury, but a matter of law on bank interest. Scholars who forbid bank interest consider that bank interest is riba, while scholars who allow it believe that it is not riba. Keywords: conventional economics, Islamic economics, Islamic studies